James vs his future self [videorecording (DVD)] - Chernick, Jonas, 1973-; Stern, Daniel; Conroy, Frances; Spencer-Nairn, Tara (Gravitas Ventures, 2020)
When an uptight young scientist won't listen to his future self and give up his dream of time travel, it becomes a battle of man versus himself.